ASSESSING THE EFFECT OF BIOCHAR ADDITION IN GROWING MEDIUM ON PLANT GROWTH PERFORMANCE OF BOK CHOY (Brasicca Rappa Subsp. Chinensis) USING SUSTAINABLE SOILLESS AGRICULTURE SYSTEM - Siti Nurlia Ali; Azlan Abdul Aziz; Nur Nasulhah Kasim; Shahairatulraiza Ahmad Tajuddin; Nur Faezah Omar; Noraini Nasirun @ Hirun (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
COVID-19 pandemic has revealed several extreme weather conditions which caused damage to nature and decrease in crop production. This has resulted to increased demand for food and raise concerns related to food security such as issues of hunger and poverty. Soilless agriculture has become a preferable approach to curb this issue due to benefits such as preventing soil-related disease and deforestation. Soilless agriculture uses biomass like cocopeat as growing medium. Previously, biochar has shown a better result in plant growth as compared to cocopeat media alone, but unsuitable concentration could be ineffective or induce plant disease. Hence, in this study, the influence of biochar added into the growing medium was investigated on the growth of Bok Choy (Brassica rapa subsp. Chinensis) using the sustainable Zero-Energy Soilless Agriculture (ZESA) System. Three treatments of growing medium T1 (100% cocopeat), T2 (82% cocopeat, 18% biochar), and T3 (63% cocopeat, 37% biochar), were conducted using Completely Randomized Design (CRD) to design the plot treatment. The plant growth parameters of height, number of leaves, and fresh weight were observed for 28 days at 7 days intervals. The results indicated that T1 exhibited the highest number of new leaves (3 – 4 leaves per week), plant height (4.7 cm) and fresh weight (53.87 g), followed by T2 and T3. Analysis of variance (ANOVA) revealed that biochar addition has significant difference in means treatments of 0.029 between T1 and T2. Interestingly, T3 has the potential as a good growing medium as analysis of leaves after harvesting showed that this growing medium promotes N uptake of the plant as compared to other treatments.